Product Innovation and Success of Telecommunication Companies in Nigeria - Adakole, Idu John; Danja, Kabir Haruna; Kibuuka, Muhammad (KIU Journal of Social Sciences, 2017)
This study sought to establish the extent to which innovation affects business success of telecommunication companies in Nigeria. Specifically, the study sought to investigate the relationship between product innovation and business success. The study used descriptive correlational, comparative and cross-sectional survey designs. Data were collected from 355 respondents using self-administered questionnaires as the key data collection instruments. Data were analyzed using frequency counts, means, standard deviations, t-statistics, Pearson’s Linear Correlation coefficient, One way Analysis of Variance (ANOVA) and regression analysis. The findings revealed that product innovation and business success had a weak positive correlation. There was no significant difference in the level of innovation and business success in the telecommunication in Nigeria in respect to demographic characteristics of the employees. Recommendations based on the findings were that telecommunication companies should ensure continuous improvements in their products/services to cater for the ever changing consumer tastes and preferences, source for cheaper sources of raw materials and labour to reduce costs of production, create reputation for producing superior quality products, find ways to cut costs of operation to allow them more profits and get a competitive advantage over competitors, regularly promote products to remind, inform and arouse interests of consumers.
Keywords: Product Innovation; Success; Telecommunication Companies